Geometry of concircular curvature tensor of Nearly Kahler manifold - Taha H. Jasim; Ali A. Shihab; Rawaa A. Zabin (Tikrit Journal of Pure Science)
In this paper, we study the necessary condition where a nearly Kahler manifold of flat concircular tensor has been found.  And the relationship between these invariants and additional properties of symmetry concircular tensor, as well as geometrical sense of the reference (manipulation) in zero of these invariants are studied.